Anomalias magnéticas, alturas do geóide e variações de temperatura na plataforma do SW de Portugal - Duque, Maria Rosa (2023)
Geoid height values obtained with models EGM 84, EGM96 and EGM 2008 for the region under study present significant changes, ocurring in relatively short time intervals, which can be interpreted as density changes associated with temperature variations in the region. In the present work, studies were made with data of the geomagnetic field (average hourly values) obtained at the Magnetic Observatory of Coimbra, San Fernando and Almeria, and it was concluded that anomalies detected on February 27 of 1969 can be interpreted as being obtained by suprposition of additional magnetic fields (in relation to days 25 and 26th), initially with mainly horizontal component and later with mainly vertical component. These additional fields may be associated with ion movements with mainly vertical direction followed by mainly horizontal direction. The variation in the direction of the geomagnetic field and the associated electric field lines could lead to reorientation of dipolar molecules and temperature increase in the region, whixh may have caused opening cracks and fractures already existing in the region, facilitating the entry of large amounts of water to deep zones, with relatively high speeds and temperatures.